THE IMPACT OF ONLINE GAMES AND ATTITUDE CHANGES IN GRADE V STUDENTS AT MI NURUL ISLAM SEKARBELA - Aizyra Amalya Garnis (Sinar Lima, 2026)
This research is motivated by the widespread use of online games by students, which can have both negative and positive impacts on student attitudes. This study aims to determine the impact of online game use and attitude changes in grade V students at MI Nurul Islam Sekarbela. This study is a qualitative study using a descriptive approach to gather information related to the impact of online game use and attitude changes in grade V students at MI Nurul Islam Sekarbela. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used was the Miles and Huberman model: Data Condensation, Data Display, and Conclusion Drawing/Verification. The results indicate that online game use has both positive and negative impacts on students. The positive impacts of online games include improving English language skills, while the negative impacts include addiction. Online games also impact students' attitudes. These changes in students' attitudes due to online games include improving cooperation skills, negativism, aggression, and fighting.